Proton Exchange Membrane Fuel Cell with Humidifying Zone - 吕维忠 刘志祥 王诚 毛宗强 涨密林 (Chinese journal of chemical engineering, 2010)
Water management is of great importance to maintain performance and durability of proton exchange membrane fuel cells. This paper presents a novel proton exchange membrane （PEM） fuel cell with a humidification zone in the membrane electrode assembly （MEA） of each cell, in which the moisture of the cathode exhaust gas could transfer through the membrane to humidify anode or cathode dry gas. With a simple model, the relative humidity （RH） of the dry air exhaust from a membrane humidifier with 100% RH stream as a counter flow is calculated to be 60.0%, which is very close to the experimental result （62.2%）. Fuel cell performances with hydrogen humidifying, air humidifying and no humidifying are compared at 50, 60 and 70°C and the results indicate that humidifying is necessary and the novel design with humidifying zone in MEA is effective to humidify dry reactants. The hydrogen humidifying shows better performance in short term, while water recovered is limited and the stability is not as good as air humidifying. It is recommended that both air and hydrogen should be humidified with proper design of the humidifying zones in MEA and plates.